Factors Affecting Mortality in COVID-19 Pneumonia Patients Treated with Tocilizumab - Günaydın, Selda; Bektaş Aksoy, Hayriye; Aksoy, İskender and Elmas, Abdülbaki and Dülger, Ahmet Cumhur (The European Research Journal, 2026)
Objectives: Severe COVID-19 pneumonia is often complicated by hyperinflammation and multiorgan failure. Tocilizumab, an interleukin-6 receptor antagonist, has been used to mitigate cytokine storm; however, it’s prognostic impact remains uncertain. Methods: This retrospective cohort study included 43 adult patients with PCR-confirmed COVID-19 pneumonia who received tocilizumab at a tertiary hospital in Turkiye between April and September 2020. Patients were categorized as survivors or non-survivors. Demographic data and laboratory markers were analyzed at baseline, 24 hours, and 7 days post-treatment. Statistical analyses included Mann–Whitney U, Wilcoxon signed-rank, and chi-square tests. Results: Non-survivors were significantly older (mean age: 72.4 vs. 64.9 years, P=0.046) and had higher levels of C-reactive protein (P=0.002), D-dimer (P=0.004), procalcitonin (P= 0.001), troponin (P=0.004), BUN (P<0.001) and creatinine (P=0.02). Survivors showed higher albumin and prognostic nutritional index (PNI) values (P=0.009 and P<0.001, respectively). On day 7, survivors exhibited increased lymphocyte, eosinophil, and platelet counts, while non-survivors had persistent neutrophilia, leukocytosis, and elevated neutrophil-to-lymphocyte ratios (P<0.05). Dynamic biomarker trends suggested ongoing inflammation and prothrombotic states among non-survivors. Conclusions: Tocilizumab therapy may be more effective when administered early and in patients with preserved nutritional and immune function. Advanced age, renal dysfunction, elevated inflammatory markers, and poor nutritional status were significant predictors of mortality. Further prospective studies are warranted to validate these findings.